Metataxonomic and Metagenomic Approaches vs. Culture-Based Techniques for Clinical Pathology - Hilton, Sarah K.; Castro-Nallar, Eduardo; Pérez-Losada, Marcos; Toma, Ian; McCaffrey, Timothy A.; Hoffman, Eric P.; Siegel, Marc O.; Simon, Gary L.; Johnson, W. Evan; Crandall, Keith A. (Frontiers in Microbiology, 2016)
Diagnoses that are both timely and accurate are critically important for patients with life-threatening or drug resistant infections. Technological improvements in High-Throughput Sequencing (HTS) have led to its use in pathogen detection and its application in clinical diagnoses of infectious diseases. The present study compares two HTS methods, 16S rRNA marker gene sequencing (metataxonomics) and whole metagenomic shotgun sequencing (metagenomics), in their respective abilities to match the same diagnosis as traditional culture methods (culture inference) for patients with ventilator associated pneumonia (VAP). The metagenomic analysis was able to produce the same diagnosis as culture methods at the species-level for five of the six samples, while the metataxonomic analysis was only able to produce results with the same species-level identification as culture for two of the six samples. These results indicate that metagenomic analyses have the accuracy needed for a clinical diagnostic tool, but full integration in diagnostic protocols is contingent on technological improvements to decrease turnaround time and lower costs.